Positive Urine Morphine Test in a Chinese Patient Receiving Methadone Maintenance Treatment After Eating Hot Pot: A Case Report - Ma, Jun; He, Yafei; Zeng, Kuan; Liu, Xuebing (Frontiers in Psychiatry, 2020)
Poppy shells contain opioids. It is a popular, but illegal spice in China. If these shells are added to food, urine morphine test of the patients involved in methadone maintenance treatment (MMT) can turn out positive. A 44-year-old male patient, who had been receiving MMT for 12 years with an extremely good treatment adherence, presented with positive urine morphine test in routine clinical compliance monitoring. However, the patient denied the use of any opioids recently. Coincidently, all of his four family members (none with a history of heroin abuse) showed positive results in urine morphine test. Considering that all these people ate a hot pot together a day before the test added to the speculation that the positive result could be due to the addition of poppy shell to the hot pot. Based on our results, we propose that this unusual phenomenon is worthy of clinical attention when managing patients at MMT clinics.